Whatever - Suzanne, Jamie; Pascal, Francine; Copyright Paperback Collection (Library of Congress) (New York : Bantam Books, 2000)
Lacey looks forward to her mother's visit as a chance to bond with her and perhaps to leave life with her father and stepmother to share her mother's glamorous life in New York, but things don't turn out the way she had hoped.
Keywords: Mothers and daughters -- Fiction; Stepfamilies -- Fiction; Junior high school students -- Fiction; Domestic fiction; Young adult fiction